Foot and mouth disease prevalence in cattle and buffaloes from India determined by systematic review and meta-analysis - Krishnamoorth, P; KARTHIKA, N; SANGEETHA, T R; SURESH, K P; SRIDEVI, R; SHOME, B R (The Indian Journal of Animal Sciences, 2022)
In the present study, Foot and Mouth Disease (FMD) prevalence in cattle and buffaloes from India was determined by employing systematic review and meta-analysis. The FMD prevalence studies (73) reported during 1986-2021 were obtained from online databases, offline literatures and meta-analysis by using meta package in R-Software was done. The pooled FMD prevalence in India was 43% (95% level CI 35-52%, PI 3-94%) obtained by using 5,00,267 samples. Period-wise analysis revealed a higher prevalence of 68% during 1986-2000 than recent years. A higher FMD prevalence in east zone (59%), and lower in central zone (24%) was observed. Among 19 states, a higher prevalence of FMD was detected in Rajasthan (81%) and lower in Andaman and Nicobar (3%). Species-wise analysis indicated a higher prevalence in cattle (45%) than buffaloes (30%). The method-wise analysis revealed a higher prevalence in antigen detection (49%) than the antibody detection (42%) methods. The FMD seroprevalence was 59% against the FMD vaccination obtained by liquid phase blocking ELISA. In India, a higher FMD prevalence by serotype O (64%) than other serotypes was observed. Thus, the higher FMD prevalence zone, states, species, methods and serotypes identified may be employed by policy makers for making informed decisions to maximise the use of scarce resources available. There was a decreasing trend in FMD prevalence in the recent years, however, need is there to prevent FMD by vaccination to move in the progressive control pathway stages. This will help in increasing export trade and eventually result in economic benefits to dairy farmers